Intersubband Optical Nonlinearity of GeSn Quantum Dots under Vertical Electric Field - Mourad Baira; Bassem Salem; Niyaz Ahamad Madhar; Bouraoui Ilahi (Micromachines, 2019)
The impact of vertical electrical field on the electron related linear and 3rd order nonlinear optical properties are evaluated numerically for pyramidal GeSn quantum dots with different sizes. The electric field induced electron confining potential profile’s modification is found to alter the transition energies and the transition dipole moment, particularly for larger dot sizes. These variations strongly influence the intersubband photoabsorption coefficients and changes in the refractive index with an increasing tendency of the 3rd order nonlinear component with increasing both quantum dot (QD) size and applied electric field. The results show that intersubband optical properties of GeSn quantum dots can be successively tuned by external polarization.